2023
DOI: 10.1002/dta.3529
|View full text |Cite
|
Sign up to set email alerts
|

Unauthorized ingredients in “nootropic” dietary supplements: A review of the history, pharmacology, prevalence, international regulations, and potential as doping agents

Karol Jędrejko,
Oliver Catlin,
Timothy Stewart
et al.

Abstract: The first nootropic prohibited in sport was fonturacetam (4-phenylpiracetam, carphedon) in 1998. Presented here 25 years later is a broad-scale consideration of the history, pharmacology, prevalence, regulations, and doping potential of nootropics viewed through a lens of 50 selected dietary supplements (DS) marketed as "cognitive enhancement," "brain health," "brain boosters," or "nootropics," with a focus on unauthorized ingredients. Nootropic DS have risen to prominence over the last decade often as multico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 157 publications
0
6
0
Order By: Relevance
“…91 The analytes exhibited molecular masses of 3.8 and 4.2 kDa, respectively, and the extraction from plasma was shown to be particularly efficient when combining protein precipitation with subsequent mixed-mode cation-exchange SPE. LODs were determined with 0.5 ng/mL, and by means of isotope-labeled reporter ion screening using 13…”
Section: Hormone and Metabolic Modulatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…91 The analytes exhibited molecular masses of 3.8 and 4.2 kDa, respectively, and the extraction from plasma was shown to be particularly efficient when combining protein precipitation with subsequent mixed-mode cation-exchange SPE. LODs were determined with 0.5 ng/mL, and by means of isotope-labeled reporter ion screening using 13…”
Section: Hormone and Metabolic Modulatorsmentioning
confidence: 99%
“…More than 50% of the study participants declared the use of dietary supplements, 9,10 and data suggest that such dietary supplement use is, to some extent, also a gateway to the use of prohibited performance enhancing substances. 11,12 Besides, the issue of contaminated and adulterated dietary supplements resulting in AAFs during doping controls still exists, both in manufactured and compounded products, 13,14 which substantially increases the risk of AAFs and ADRVs as well as health issues as recently outlined by Pascali et al 15 and Tran et al 16 Advancing test methods for doping controls is vital for modern sports drug testing programs, 17 as demonstrated by attributable effects and impact 18 as well as their implementation into routine application at major sporting events. 19,20 Research aiming at facilitating such advances are commonly aligned with the World Anti-Doping Agency's (WADA's) Prohibited List 21 and its 11 classes of banned substances (S0-S9 plus P1) and three categories of prohibited methods (M1-M3) (Table 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among those, PFS advertised for cognitive enhancement, as they contain nootropic plants as ingredients, have risen in prominence worldwide, and their possible adulteration has been highlighted by different studies [ 52 ]. The direct use of nootropic substances, such as the pharmaceutical stimulant Adderall, is known to occur by a variety of consumers, including students, the military, and night-shift workers, who seek increasing concentration and focus, performance enhancement, and fatigue reduction [ 53 ]. Among college students, studies have reported the illegal use of compounds such as modafinil and methylphenidate, which were developed to treat disorders such as attention deficit, narcolepsia, and/or dementia-like diseases, and even illegal compounds, such as cocaine and amphetamines [ 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides PFS used for cognitive enhancement, other supplements used for different purposes but also related to brain activity, such as mood or sleep improvement, are also increasingly available in the market. Altogether, the global market for brain health supplements was estimated at USD 8.2 billion in 2022 and is expected to grow to more than USD 15 billion by 2030 [ 53 ]. As far as the literature consulted, data on the consumption prevalence of supplements to improve mood or sleep are still scarce or non-existent.…”
Section: Introductionmentioning
confidence: 99%